Dysregulation of Anti-Inflammatory Annexin A1 Expression in Progressive Crohns Disease - Sena, Angela; Grishina, Irina; Thai, Anne; Goulart, Larissa; Macal, Monica; Fenton, Anne; Li, Jay; Prindiville, Thomas; Oliani, Sonia Maria [UNESP]; Dandekar, Satya; Goulart, Luiz; Sankaran-Walters, Sumathi (Public Library Science, 2013)
Background: Development of inflammatory bowel disease (IBD) involves the interplay of environmental and genetic factors with the host immune system. Mechanisms contributing to immune dysregulation in IBD are not fully defined. Development of novel therapeutic strategies is focused on controlling aberrant immune response in IBD. Current IBD therapy utilizes a combination of immunomodulators and biologics to suppress pro-inflammatory effectors of IBD. However, the role of immunomodulatory factors such as annexin A1 (ANXA1) is not well understood. The goal of this study was to examine the association between ANXA1 and IBD, and the effects of anti-TNF-alpha, Infliximab (IFX), therapy on ANXA1 expression.Methods: ANXA1 and TNF-alpha transcript levels in PBMC were measured by RT PCR. Clinical follow up included the administration of serial ibdQs. ANXA1 expression in the gut mucosa was measured by IHC. Plasma ANXA1 levels were measured by ELISA.Results: We found that the reduction in ANXA1 protein levels in plasma coincided with a decrease in the ANXA1 mRNA expression in peripheral blood of IBD patients. ANXA1 expression is upregulated during IFX therapy in patients with a successful intervention but not in clinical non-responders. The IFX therapy also modified the cellular immune activation in the peripheral blood of IBD patients. Decreased expression of ANXA1 was detected in the colonic mucosa of IBD patients with incomplete resolution of inflammation during continuous therapy, which correlated with increased levels of TNF-alpha transcripts. Gut mucosal epithelial barrier disruption was evident by increased plasma bacterial 16S levels.Conclusion: Loss of ANXA1 expression may support inflammation during IBD and can serve as a biomarker of disease progression. Changes in ANXA1 levels may be predictive of therapeutic efficacy.